1953
DOI: 10.1021/j150508a019
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibition of Foaming. V. Synergistic Effects of Antifoaming Agents

Abstract: Synergistic effects of antifoaming agents are investigated for foams of two synthetic detergents, Aerosol OT and Nacconol NRSF. The defoaming systems are (a) mixtures of Ucon 50-HB-3520 and 2-ethylhexanol and (b) mixtures of tributyl phosphate and methylisobutylcarbinol. The first of these shows a correspondence between antifoaming action and the free energy of spreading of the antifoam composition on the detergent solution. The second system shows no such correspondence, but a more complex effect related to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1970
1970
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This isdue to spontaneous spreading caused by a decrease in free energy [II. Itowever, -Ross et al [111] observed the existence of a correspondence between foam stability and the free energy of spreading (numerically equa;1 but opposite in sign Lo tilt spreading coefficient) of the eontlfoam on one fo_rning solution _nd the l_ck of correspondence for another systern,…”
Section: Presence Of Oilmentioning
confidence: 98%
“…This isdue to spontaneous spreading caused by a decrease in free energy [II. Itowever, -Ross et al [111] observed the existence of a correspondence between foam stability and the free energy of spreading (numerically equa;1 but opposite in sign Lo tilt spreading coefficient) of the eontlfoam on one fo_rning solution _nd the l_ck of correspondence for another systern,…”
Section: Presence Of Oilmentioning
confidence: 98%
“…In the literature there has, however, been scattered speculation as to the role of the above two antifoam components (Bhute, 1971;Pattle, 1950;Povich, 1975; Robinson and Wood, 1948; Ross, 1950Ross, , 1967; Ross et al, 1953; Ross and McBain, 1944;Ross and Young, 1951). It was first believed that the spontaneous spreading of silicone oil over the bubble surface is primarily responsible for bubble rupture (Pattle, 1950;Ross, 1950) and that the presence of silica filler increases the spreading pressure and improves dispersibility of silicone oil simply by reducing the interfacial tension between silicone oil and the aqueous solution.…”
Section: Introductionmentioning
confidence: 99%